Posttraumatic Scrotal Reconstruction with a Pedicled “Extended” Superficial Circumflex Iliac Artery Perforator Flap: A Case Report - Sisternas Hernández, Lucía; López Fernández, Susana; Zamora Alarcón, Paúl D.; Vega García, Carmen; Torrano Romero, Laura; Fernández Garrido, Manuel (Archives of Plastic Surgery, 2024)
The superficial circumflex iliac artery (SCIA) perforator (SCIP) flap has been used for scrotal reconstruction after Fournier's gangrene, skin cancer, or infections. However, there are few publications with regard to penoscrotal reconstruction after a traumatic injury with this flap. In this article, we propose a new SCIP flap variation, the “extended” or “direct” SCIP flap, to effectively reconstruct a wide scrotal defect after a traumatic injury. The “extended” SCIP flap is designed medial and cranial to the anterosuperior iliac spine (ASIS) using the superficial branch of the SCIA as the main pedicle.
Keywords: penoscrotal reconstruction; SCIP flap; pedicled flap